Introduction: Ulf Hannerz and the Militant Middle Ground - Garsten, Christina; Eriksen Hylland, Thomas; Randeria, Shalini (Anthropology Now and Next, 2014)
Ulf Hannerz’ published work spans more than four decades to date and has, since the beginning, contributed to shaping and reshaping the world of anthropology. The very titles of some of his major books—Soulside(1969),Exploring the City(1980),Cultural Complexity(1992),Transnational Connections(1996),Foreign News(2004), andAnthropology’s World(2010)—reveal an anthropologist who has consistently been ahead of his time in exploring subjects that were not yet the academic fashion. Yet he has been both conversant with, and drawing energy from, his peers and the traditions of the discipline on both sides of the Atlantic, just